2018
DOI: 10.1103/physreva.97.013851
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon quantum Rabi model with superconducting circuits

Abstract: We propose a superconducting circuit to implement a two-photon quantum Rabi model in a solid-state device, where a qubit and a resonator are coupled by a two-photon interaction. We analyze the input-output relations for this circuit in the strong coupling regime and find that fundamental quantum optical phenomena are qualitatively modified. For instance, two-photon interactions are shown to yield single-or two-photon blockade when a pumping field is either applied to the cavity mode or to the qubit, respective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
168
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(169 citation statements)
references
References 100 publications
(143 reference statements)
0
168
0
Order By: Relevance
“…Notice that in the literature the TPI term is often written asσ (i) x â † a † +ââ , whereas we take here the interaction Hamiltonian to be in the full-quadratic form. The latter form of the interaction arises when the qubit is coupled to the square of the electric (or magnetic) field of the cavity mode and it is therefore a natural generalization of the standard dipolar coupling [19]. The system spectrum is shown in Figure 1a,b for N = 1 and N = 3, as a function of the coupling strength g 2 .…”
Section: The Spectral Collapsementioning
confidence: 99%
See 2 more Smart Citations
“…Notice that in the literature the TPI term is often written asσ (i) x â † a † +ââ , whereas we take here the interaction Hamiltonian to be in the full-quadratic form. The latter form of the interaction arises when the qubit is coupled to the square of the electric (or magnetic) field of the cavity mode and it is therefore a natural generalization of the standard dipolar coupling [19]. The system spectrum is shown in Figure 1a,b for N = 1 and N = 3, as a function of the coupling strength g 2 .…”
Section: The Spectral Collapsementioning
confidence: 99%
“…In particular, it was shown that in the context of circuit QED it is possible to engineer an intrinsically nondipolar coupling between a flux qubit and a microwave resonator. In this way, dipolar and two-photon interaction terms can be selectively activated [19] and, in the case of galvanic coupling, the interaction strength can be pushed into the USC regime [20]. In the following, we will briefly introduce the spectral properties of TPI models and we will show how they affect the optical response of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these interaction regimes, several properties of coupled light-matter systems change drastically, opening the way to a wealth of new intriguing physical effects (see, e.g. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]) which may offer opportunities for the development of quantum technologies [36][37][38][39][40][41][42][43][44].…”
mentioning
confidence: 99%
“…When the interaction energy is a small perturbation on the free energies, the quantum Rabi model can be reduced to the well-known Jaynes-Cummings (JC) model [18] through the rotating-wave approximation, which describes the usual coherent exchange of a quantum of energy between a two-level atom and a single-mode bosonic field.The JC model can be extended to nonlinear versions (nondipolar light-matter interaction) [19], in particular the multiphoton JC model [20,21] that considers multiphoton exchange. Such a nonlinear Hamiltonian appears, at least for two-photon interaction, in trapped-ion domain [22,23], optical [24] and microwave [25] cavities, or even in superconducting circuits [26][27][28][29][30]. In Refs.…”
mentioning
confidence: 99%